Cross-border knowledge pipelines and innovation performance of chinese firms: Evidence from Zhangjiang in Shanghai - Gang Zeng; Yi Zhang; Xianzhong Cao (ZFW - Advances in Economic Geography, 2023)
It is increasingly emphasized that firms' innovation depends on external knowledge interaction in the field of economic geography. Global knowledge linkages and interaction plays crucial role in gaining competitive advantage for firms in developing countries because of their immature innovation systems, inspiring a wide academic interest around cross-border knowledge pipelines. However, the existing literature has been silent about the type in which firms employ cross-border knowledge pipelines and neglects the potential importance of firm's ownership in this process. Using 2015 survey micro-data of 4685 Chinese firms in Zhangjiang National Innovation Demonstration Zone, we investigate how different types of cross-border knowledge pipelines indicated by foreign R&D investment and returnees influence firm's innovation. The research highlights the positive effects of foreign R&D investment and returnees on firms' patent innovation, while returnees exerts negative influence on firms' product innovation. Moreover, there exists a complementary relation between foreign R&D investment and returnees in facilitating firm's patent innovation. State ownership negatively affects the relationship between foreign R&D investment and firms' patent innovation.
Keywords: 330; Chinese firms; Cross-border knowledge pipelines; innovation performance